Java EE 8 Cookbook - Moraes Elder (Packt Publishing, 2018)
Java EE is a collection of technologies and APIs to support Enterprise Application development. The choice of what to use and when can be dauntingly complex for any developer. This book will help you master this. Packed with easy to follow recipes, this is your guide to becoming productive with Java EE 8. You will begin by seeing the latest features of Java EE 8, including major Java EE 8 APIs and specifications such as JSF 2.3, and CDI 2.0, and what they mean for you. You will use the new features of Java EE 8 to implement web-based services for your client applications. You will then learn to process the Model and Streaming APIs using JSON-P and JSON-B and will learn to use the Java Lambdas support offered in JSON-P. There are more recipes to fine-tune your RESTful development, and you will learn about the Reactive enhancements offered by the JAX-RS 2.1 specification.